Eye movements and ERP biomarkers for face processing problems in avoidant attachment-style individuals - Gu, Simeng; Jiang, Yao; Liu, Mei; Li, Yumeng; Liang, Yuan; Feng, Rou; Xu, Minghong; Wang, Fushun; Huang, Jason H. (Frontiers in Behavioral Neuroscience, 2023)
Background Avoidant attachment poses a serious risk to intimate relationships and offspring. However, there are few studies on the face-processing characteristics and impairments of avoidant individuals based on basic emotion theory. Therefore, this study investigated the issues of emotional processing and deactivation strategies in individuals with avoidant attachment. Methods Avoidant and secure individuals were recruited to participate in an eye-tracking experiment and a two-choice oddball task in which they had to distinguish facial expressions of basic emotions (sadness, anger, fear, disgust, and neutral). Eye fixation durations to various parts of the face, including the eyes, nose, and mouth, were measured, and three event-related potentials (ERP) components (P100, N170, and P300) were monitored. Results Avoidant individuals could not process facial expressions as easily as secure individuals. Avoidant individuals focused less on the eyes of angry faces when compared to secure individuals. They also exhibited a more positive P100 component and a less negative N170 component when processing faces and a larger amplitude of the P300 component than secure individuals when processing emotional expressions. Conclusion Avoidant individuals use deactivating strategies and exhibit specific characteristics at different stages, which are of great significance in social interaction.